Seismic response of a rubble mound breakwater in Turkey - Yüksel, Y; Çetin, KÖ; Özgüven, O; Isik, NS; Cevik, E; Sümer, BM (EMERALD GROUP PUBLISHING LTD, 2004)
This paper presents analyses of seismically induced deformations at Eregli Fishery Port breakwater during the 1999 Kocaeli (Izmit), Turkey earthquake. The paper discusses: (a) observed ground deformations and displacements after the earthquake; (b) the results of field investigations by means of borings including standard penetration tests; (c) analyses of observed deformation mechanisms by a suite of methods; and (d) the possible contribution of soil liquefaction rupture on the observed deformations.
Keywords: coastal engineering; geotechnical engineering; maritime engineering; Engineering; Water Resources